Cognitive Behavioral Therapy (CBT)-Based Group Counseling to Improve Academic Self-Efficacy Among Indonesian Junior High School Students From Non-Intact Families: A Quasi-Experimental Study - Anisa Afriani; Netrawati (Journal of Educational, Health and Community Psychology, 2026)
Academic self-efficacy shapes adolescents’ motivation, persistence, and academic achievement, yet students from non-intact families may face additional barriers that undermine confidence in learning. This quasi-experimental study compared cognitive behavioral therapy (CBT)-based group counseling with conventional group counseling among 16 Indonesian junior high school students from non-intact families. Participants were all female (mean age = 13.5 years; grades 7–8) and completed a 40-item Academic Self-Efficacy Scale (score range 40–200; α = .777; content validity supported through expert review) at pretest and posttest. Wilcoxon signed-rank tests indicated significant improvements in academic self-efficacy in both groups (CBT: Z = −2.54, p = .011, r = .64; control: Z = −2.53, p = .011, r = .64). However, a Mann–Whitney U test on gain scores showed greater improvement in the CBT group than in the control group (U = 24.0, p = .022, r = .45). Overall, CBT-based group counseling appears meaningfully more effective than conventional counseling for strengthening academic self-efficacy in this vulnerable student population. Schools are recommended to integrate brief CBT-informed group modules (e.g., cognitive restructuring, goal setting, and behavioral rehearsal) within counseling services, and future studies should use larger, mixed-gender samples with follow-up assessments to examine durability and mechanisms of change.